Faith and reason in Islam - "Najjar, Ibrahim Y.(tr.)" (Oxford, 2007)
This book is acknowledged as the leading transmitter of Aristotelian thought, Averroes also held controversial views about the relationship between faith and reason, arguing that religion should not be allowed to impose limits on the exercise of rational thought. His theory of rationality, along with others on language, justice and the interpretation of religious texts, is clearly presented here, in a work that provides the most comprehensive picture available of Averroes's great intellectual achievements.
Keywords: Islam